Blue Circular Economy—Reuse and Valorization of Bivalve Shells: The Case of Algarve, Portugal - Magalhães, Fernanda Caroline (2024)
The Circular Economy emerges as an alternative to reinvent the linear production model (take–make–waste), focusing on reintegrating waste into the production cycle, and aiming to minimize both environmental disposal and the unrestrained extraction of raw materials. In this context, the concept of Blue Economy arises, an approach centered on preserving and valorizing marine and coastal resources. This article aims to develop a model for the circuit of bivalve shells, emphasizing the transformation of the residues into new products and identifying how these processes affect sociocultural, economic, and environmental dimensions. The methodology involved the surveying of local stakeholders directly involved in bivalve production and consumption to identify the relationship of these stakeholders with the production, marketing, and disposal of bivalves. It is concluded that biowaste has potential, and there is interest among local stakeholders in reusing it, but a lack of knowledge and connection among stakeholders ultimately leads to the devaluation of the product. The circuit of bivalves is necessary to identify value, propose correct collection, and stimulate interest in their reuse, both by other industries and by the aquaculture industry itself. Exploring the potential for reusing bivalves and mitigating their waste, as well as preventing improper disposal, could drive the development of the Blue Circular Economy in coastal regions.